The Two Methods of Reverse Overshoot Suppression in Automation Systems; Journal of Telecommunication, Electronic and Computer Engineering; Vol. 9, № 2-2 - Zhmud V. A. Vadim Arkadjevich; Pyakullya B. I. Boris Ivanovich; Semibalamut V. M. Vladimir Mikhaylovich; Trubin M. V. Maksim Vitaljevich; Yadryshnikov O. D. Oleg Dmitrievich (2017, 2017)
Title screen